Artificial Intelligence Tools in Higher Education Students Usage Analysis – Case Study: Sampoerna University - Rahim, Noorfi Azizah; Hanum, Az Zahra Azizah; Bhakti, Muhammad Agni Catur; Wandy, Wandy (Jurnal Teknologi, 2023)
The potential application of AI in education has become an area captivating the younger generation. Among higher education students, AI tools support academic activities by providing students with personalized learning experiences that digitize each student's needs and abilities. This research aims to determine the adoption of AI tools in academic areas, specifically at Sampoerna University. This research contributes to the socialization of the use of AI tools to support academics in a good and correct way. This research used a combination of quantitative and qualitative surveys as primary data. Results show that using AI tools has become common among Sampoerna University students and has gained importance in supporting their academic needs. 50% of respondents used the AI tools in less than six months, and the most used AI tool was for grammar checking. Tablet device was the least used by the students to use the AI tools, with only 6.09%.